Impact of correct anatomical slab segmentation on foveal avascular zone measurements by optical coherence tomography angiography in healthy adults - Felix Rommel; Fynn Siegfried; Maximilian Kurz; Max Philipp Brinkmann; Matthias Rothe; Martin Rudolf; Salvatore Grisanti; Mahdy Ranjbar (Journal of Current Ophthalmology, 2018)
Purpose: To evaluate the impact of correct anatomical slab segmentation on foveal avascular zone (FAZ) dimensions in the superficial capillary plexus (SCP) and deep capillary plexus (DCP) using optical coherence tomography angiography (OCTA). Methods: Participants with healthy retinas were recruited, and 5 × 5 mm OCTA images were acquired using the Canon HS-100 Angio eXpert module. FAZ size was measured in automatically (AS, manufacturer-based) and manually (MS, anatomical-based) segmented OCTA slabs by two experienced graders. FAZ dimensions, inter-rater agreement, and correlation to demographic and retinal parameters were evaluated. Results: A total of 38 eyes from 20 healthy adult subjects were included in this cross-sectional study. While in AS slabs, the FAZ in the SCP was smaller than in the DCP, in MS images, it was the opposite. MS had a relevant impact on inter-rater agreement of FAZ measurements in the SCP. The FAZ area in both plexus correlated inversely with the central retinal thickness (CRT), irrespective of the segmentation applied. Furthermore, an enlargement of FAZ size in the DCP with increasing age was found. Finally, the FAZ in female participants was significantly larger than in their male counterparts, regardless of the evaluated plexus and chosen segmentation. Conclusions: Correct anatomical slab segmentation has a significant impact on FAZ size measurements. Not adjusting the segmentation boundaries represents a significant source of error for measuring FAZ area and confounds comparisons across studies as well as OCTA devices. Keywords: Foveal avascular zone, Optical coherence tomography, Optical coherence tomography angiography, Slab segmentation